Kerjasama Pemerintah Kota Semarang (Dinas Kebudayaan dan Pariwisata) Dengan Kelompok Sadar Wisata (POKDARWIS) Pandanaran Dalam Pemberdayaan Masyarakat Melalui Pengembangan Desa Wisata Kandri Semarang - Dewani, Ika; Adnan, Muhammad; Adhi, Suwanto (Journal of Politic and Government Studies, 2017)
ABSTRACTKandri tourism village is one of the leading tourist village in Semarang City which is now continuously developed to be an economic support in the region, especially in Kandri Village. In the development of this Kandri tourism village, Semarang City Government through the Department of Culture and Tourism of Semarang City cooperates with Pandanaran Tourism Awareness Group (Pokdarwis) Pandanaran in terms of training and coaching. This research analyzes the cooperation between Semarang City Government (Culture and Tourism Office) and Pandanaran Tourism Awareness Group (Pokdarwis) in community empowerment through development of Kandri tourism village starting from cooperation form, cooperation implementation, result of cooperation and benefit from this cooperation. In conducting this research, researches use qualitative research methods that will produce descriptive data. This research was conducted in Kelurahan Kandri. Data obtained by researchers from documents, observations and interviews. From the results of this study, found a form of cooperation undertaken by the Department of Culture and Tourism Semarang City with Aware Group (Pokdarwis) Pandanaran is in the form of training and fostering the development of tourism conscious groups, tour guide instructors, cultural development Kandri, how to processand package/ linkage Tourism products, breedingof fish seeds and training to arrange rooms for tourist (homestay). Implementation of cooperation using informal communication such as discussion and in this cooperation there is no MOU or work agreement. The result of this cooperation is the capacity of Human Resources (HR) increased, the formation of tour packages, and the number of tourist visits also increased. Butin the implementation of community empowerment cooperation through the development of this tourist village there are obstacles that is still difficult to change mindset Kandri village people who formerly as farmers and now have to turn into business actors in the field of tourism.Key Words: Cooperation, Empowerment, Tourism Village Development